An analysis of consumer awareness and the justifications used by consumers of ‘perceived’ unethical practice: An application of Neutralization Theory in animal consumption. - Reyes-Alzate, Andres ARA (2015)
Ethical consumption has been a topic of interest in business ethics for centuries but it has only risen to prominence in the last two decades according to Crane and Matten (2007). These authors define Ethical consumption as:”…the conscious and deliberate choice to make certain consumption choices due to personal beliefs and values” (Crane and Matten, 2007, p.341). There is a plethora of investigations and debate into what makes a consumer act ‘ethically’, almost referring and analysing the actions of a niche, but what happens when we turn the tables and ask those that actively decide against not participating in these ‘ethical’ consumption patterns is what this paper aims to explore through justification theory, focussing on Neutralization Theory by Matza and Skyes (1957).